Investigation of γ-γ coincidence counting using the National Nuclear Array (NANA) as a primary standard. (April 2018) - Collins, S.M.; Shearman, R.; Keightley, J.D.; Regan, P.H.
Abstract: The National Physical Laboratory has recently been in the process of commissioning a multi-detector γ ray array - the National Nuclear Array (NANA). In this study we have sought to exploit the NANA and the excellent timing characteristics of its intrinsic LaBr3 (Ce) scintillation detectors for use as a primary standardisation system. For this initial investigation, the absolute standardisation of 60 Co has been performed by the γ-γ coincidence technique using NANA and the result compared to the established 4π(LS)-γ Digital Coincidence Counting (DCC) system. The effect of the angular correlation of the stretched E2 transitions emitted from the 4 + → 2 + → 0 states of 60 Ni on the activity determined by NANA was observed between the pairs of detectors. Corrections for these angular correlations were derived through Monte Carlo simulations. An activity per unit mass by NANA of 330.8 (10) kBq g −1 for the 60 Co solution was determined. There was no significant statistical difference between the results of NANA and the 4π(LS)-γ DCC, with a relative difference of 0.04% observed. This study shows that NANA can be used as a primary standard. Highlights: The multi-γ ray detector National Nuclear Array has been investigated for use as a primary standard. Absolute standardisation of 60 Co performed using the γ-γ coincidence technique. Effect of angular correlations on the activity determined clearly observed. Corrections for angular correlation determined through Monte Carlo simulations. γ-γ coincidence technique in agreement with the 4π(LS)-γ Digital Coincidence Counting technique.